Children's Immunization Status and Family Size of Doctor'S FaMilies in Dr. Pirngadi Haspital Medan - Johnny Arsyad; Fuad Arsyad; Chairuddin P. Lubis; Helena Siregar (Indonesian Pediatric Society, 1985)
A study of children’s immunization status and family size of doctor’s families in Dr. Pirngadi Hospital, Medan, lndonesia had been conducted on December 1982. The study was done by distributing questionaires to 105 doctors. From this study we found 247 children consisting of 19 children under 1 year of age and 228 over 1 year. Basic immunization had been done in 177 children (71.66%). Most of them had been vaccinated against Tuberculosis (95.95%). but only 2 children had been vaccinated against Measles (0.81%). The doctors who had 2 children were 30.47% and mean of total wanted children was 3.30. Awareness of immunization besides BCG and family planning should be increased among the doctors in Dr. Pinrgadi Hospital.